Proposal of a CLT reinforcement of old timber floors - Roensmaens, Bertrand (2019)
Despite the fact that, from the mechanical point of view, there is no ageing issues of timber elements when they are properly used, many old timber structures require important interventions because of changes in uses (which modifies the regulating rules for example), of material decay (misuse of timber) or possibly of a faulty design or construction. In particular, timber floors in old structures often present large deflections and most the time had been designed for a maximum load much lower than the one prescribed by contemporary rules. After an introduction about timber floors and a short review about the reinforcement technics that exist, the present paper presents a new proposal for their reinforcement. The solution developed in the present paper uses a Cross Laminated Timber (CLT) panel screwed over the existing floor, keeping a small gap between the panel and the existing joists. In this way, the new “composite” floor presents higher stiffness and the gap is used for horizontal line runs. For the design of such a “composite floor”, modified Johanssen’s equations (including the gap between the CLT panel and the joists) are proposed and their application on a case study is presented.